Advantages of Cardiac Magnetic Resonance Imaging for Severe Pectus Excavatum Assessment in Children - Dore, Mariela; Triana Junco, Paloma; Bret, Monserrat; Gomez Cervantes, Manuel; Muñoz Romo, Martha; Jimenez Gomez, Javier; Perez Vigara, Ana; Parron Pajares, Manuel; Luis Encinas, Jose; Hernandez, Francisco; Martinez, Leopoldo; Lopez Santamaria, Manuel; De La Torre, Carlos (European Journal of Pediatric Surgery, 2018)
Aim Cardiac function can be impaired in patients with pectus excavatum (PE) due to anatomic and dynamic compression of the heart. Efforts for radiation dose reduction in imaging techniques have allowed cardiac magnetic resonance imaging (c-MRI) to play a major role in PE assessment. The aim of our study is to describe the findings of c-MRI 18 months after we changed the PE assessment protocol from chest computed tomography to c-MRI.Patients and Methods Since mid-2015 all patients with severe PE (suspected Haller's index > 3.2) were assessed with inspiratory and expiratory c-MRI. A retrospective analysis of these patients was performed evaluating the following parameters: (1) Radiologic PE indexes (Haller's, correction and asymmetry indexes; and sternal rotation) and (2) cardiac function (including left and right ventricle ejection fraction).Results A total of 20 patients met the inclusion criteria. Dynamic imaging showed a significant difference during inspiration and expiration of the Haller's index 3.85 (range: 3.17–7.3) versus 5.10 (range: 3.85–10.8) (p < 0.05), and correction index (26.86% vs. 36.84%, respectively, p < 0.05). The sternal rotation was 14.5 (range: 0–36). c-MRI analysis disclosed a right ventricle ejection fraction of 50.3%. (normal range: 61% [54–71%]). Echocardiographic imaging underestimated the functional repercussion of PE in all patients.Conclusion Initial results show that PE assessment by c-MRI allows a radiation-free image of the chest wall deformity during the entire breathing process. Also, it permitted the evaluation of the influence of sternum impingement on cardiac function. These findings allowed us a careful surgical evaluation and preoperative planning.
Keywords: pectus excavatum; cardiac MRI; children; preoperative assessment